Comparison of Fecal Calprotectin Methods for Predicting Relapse of Pediatric Inflammatory Bowel Disease. (16th April 2017) - Kittanakom, Saranya; Shajib, Md. Sharif; Garvie, Kristine; Turner, Joceline; Brooks, Dan; Odeh, Sufian; Issenman, Robert; Chetty, V. Tony; Macri, Joseph; Khan, Waliul I.
Abstract : Background. Pediatric inflammatory bowel disease (IBD) is on the rise worldwide. Endoscopies are necessary for IBD assessment but are invasive, expensive, and inconvenient. Recently, fecal calprotectin (FCal) was proposed as a noninvasive and specific marker of gut inflammation. We evaluated the analytical performance of three FCal assays and their clinical performance in predicting relapse in pediatric IBD. Methods. This study used 40 pediatric IBD and 40 random non-IBD patients' fecal samples. Two automated ELISAs (Bühlmann and PhiCal® Calprotectin-EIA) and an EliA (Phadia 250 EliA-Calprotectin) were used to evaluate the analytical performance. The clinical performance was assessed by PhiCal Calprotectin-EIA, EliA-Calprotectin, and Bühlmann immunochromatographic point-of-care test (POCT). Results. All assays displayed acceptable analytical performance below and above the medical decision cut-off [imprecision (CV < 10% intra-assay; <15% interassay); linearity (overall mean % deviation < 16.5%)]. The agreement with PhiCal Calprotectin-EIA was 100% and 78.6% for Bühlmann (95% CI, 87.5–100; Kappa: 1) and EliA-Calprotectin (95% CI, 60.5–89.8; Kappa: 0.32), respectively, and 63.6% between Bühlmann and EliA-Calprotectin (95% CI, 46.6–77.8; Kappa: 0.16). All assays evaluated had similar clinical performance [AUC: 0.84 (EliA-Calprotectin); 0.83 (POCT and PhiCal Calprotectin-EIA)]. Conclusion. FCal levels determined using the same method and assay together with clinical history would be a noninvasive and useful tool in monitoring pediatric IBD.